Rotenone Remarkably Attenuates Oxidative Stress, Inflammation, and Fibrosis in Chronic Obstructive Uropathy - Ying Sun; Yue Zhang; Daqiang Zhao; Guixia Ding; Songming Huang; Aihua Zhang; Zhanjun Jia (Hindawi Limited, 2014)
Mitochondrial abnormality has been shown in many kidney disease models. However, its role in the pathogenesis of chronic kidney diseases (CKDs) is still uncertain. In present study, a mitochondrial complex I inhibitor rotenone was applied to the mice subjected to unilateral ureteral obstruction (UUO). Following 7-days rotenone treatment, a remarkable attenuation of tubular injury was detected by PAS staining. In line with the improvement of kidney morphology, rotenone remarkably blunted fibrotic response as shown by downregulation of fibronectin (FN), plasminogen activator inhibitor-1 (PAI-1), collagen I, collagen III, and α-SMA, paralleled with a substantial decrease of TGF-β1. Meanwhile, the oxidative stress markers thiobarbituric acid-reactive substances (TBARS) and heme oxygenase 1 (HO-1) and inflammatory markers TNF-α, IL-1β, and ICAM-1 were markedly decreased. More importantly, the reduction of mitochondrial DNA copy number and mitochondrial NADH dehydrogenase subunit 1 (mtND1) expression in obstructed kidneys was moderately but significantly restored by rotenone, suggesting an amelioration of mitochondrial injury. Collectively, mitochondrial complex I inhibitor rotenone protected kidneys against obstructive injury possibly via inhibition of mitochondrial oxidative stress, inflammation, and fibrosis, suggesting an important role of mitochondrial dysfunction in the pathogenesis of obstructive kidney disease.